IDENTIFICATION OF PRINCIPAL YIELD ATTRIBUTING TRAITS OF INDIAN MUSTARD [BRASSICA JUNCEA (L.) CZERNJ AND COSSON] USING MULTIVARIATE ANALYSIS - K. RAY; J. DUTTA; H. BANERJEE; R. BISWAS; A. PHONGLOSA (The Bioscan, 2014)
The study is a synthesis of available information on different yield attributing traits of Indian mustard as influenced by varied irrigation schedules and sulphur levels. Pooled data of two years of study (rabi, 2010-11 and 2011-12) on nineteen traits were subjected to principal component analysis (PCA). Among the variables, test weight had the highest correlation with seed yield followed by net assimilation rate (NAR) at 40 - 75 DAS and dry matter accumulation (DMA) at 75 DAS, respectively. Out of nineteen, only two factors had eigen value greater than one and these components accounted for 72.42% of total variance. The loadings of each variable onto each component were analyzed from the rotated factor matrix obtained through varimax rotation. First component accounted for 51.84% of total variation and associations of traits that are highly correlated with seed yield among which NAR at 40 - 75 DAS and at 75 -110 DAS and test weight were most important. Second component with 20.58% of total variation had higher loadings of variables having comparatively lower association with seed yield and among those, relative growth rate (RGR) at 75-110 DAS, plant height at 110 DAS and number of siliquae per plant were most important.